2021
DOI: 10.3389/fneur.2021.639535
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality in the Rehabilitation of Motor Function of Patients With Subacute Stroke: A Meta-Analysis

Abstract: Stroke is a major cause of death and disability in adults. Conventional therapy (CT) has limited effectiveness, and therefore, various virtual reality (VR) rehabilitation programs have been designed. However, their efficacy in regaining motor function in patients with subacute stroke is questionable. Therefore, we conducted this meta-analysis to determine the efficacy of VR, compared to CT, in restoring motor function in this patient population. Up to October 10, 2020, nine electronic databases were searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 61 publications
2
16
0
1
Order By: Relevance
“…The results of this study show that the use of Kinect-based rehabilitation games improves motor function in the upper and lower limbs and balance and improves cognitive function in improving stroke patients. These results are in line with the results of other similar studies in the field of using Kinect-based rehabilitation in improving the motor function of the upper [ 69 ], lower limbs [ 70 ], balance [ 71 ], and cognition [ 72 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study show that the use of Kinect-based rehabilitation games improves motor function in the upper and lower limbs and balance and improves cognitive function in improving stroke patients. These results are in line with the results of other similar studies in the field of using Kinect-based rehabilitation in improving the motor function of the upper [ 69 ], lower limbs [ 70 ], balance [ 71 ], and cognition [ 72 ].…”
Section: Discussionsupporting
confidence: 91%
“…[ 12 ] The effectiveness of VR-based rehabilitation has been verified in Parkinson disease, stroke, and cerebral palsy. [ 11 , 13 , 14 ] In orthopedic rehabilitation, the advantage of VR-based rehabilitation has been explored in patients with osteoarthritis, low back pain, and anterior cruciate ligament injury. [ 6 , 15 , 16 ] Although some studies have investigated the effect of VR equipment on TKA patients, [ 17 , 18 ] there is insufficient evidence to demonstrate the advantage of VR.…”
Section: Introductionmentioning
confidence: 99%
“… [11] VR-based rehabilitation results in excellent outcomes for patients due to its ability to provide simulations of real environments [12] . The effectiveness of VR-based rehabilitation has been verified in Parkinson disease, stroke, and cerebral palsy [11,13,14] . In orthopedic rehabilitation, the advantage of VR-based rehabilitation has been explored in patients with osteoarthritis, low back pain, and anterior cruciate ligament injury [6,15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…There are several recently published studies, including systematic reviews and meta-analysis, which underpin the potential VR offers in gait rehabilitation. It was demonstrated that VR can support gait rehabilitation for patients with Parkinson’s Disease ( Mirelman et al, 2011 ; Lu et al, 2021 ), retrain gait symmetry ( Shideler et al, 2021 ), restore function after stroke ( Ahn and Hwang, 2019 ; Palacios-Navarro and Hogan, 2021 ; Peng et al, 2021 ), support neuro-psychomotor rehabilitation of children with cerebral palsy ( de Oliveira et al, 2016 ), improve balance and gait in older adults ( de Vries et al, 2020 ; Lee, 2020 ; Willaert et al, 2020 ; Delgado and Der Ananian, 2021 ), and is also being used to support gait training after amputation ( Darter and Wilken, 2011 ).…”
Section: Introductionmentioning
confidence: 99%